Repositioning three models of social policy with reference to East Asian welfare systems. (November 2015) - Lin, Ka; Chan, Raymond KH
This article compares features of the redistributive, developmental and productivist models of social policy. Using East Asian welfare systems as examples, it illustrates the application of the productivist and developmental models, and describes the contextual factors influencing these models. It argues that each model is an outgrowth of a particular social, economic and political context. When the context changes, the choice of model will also change, as shown in the recent development of redistributive policies in the East Asian region.